National traditions as a factor of formation of the social character of the Kyrgyz people - Musaeva N. K. (Interactive science, 2017)
this article reveals the influence of national traditions on the formation of the psychology of the Kyrgyz people. It also highlights the psychological significance of such traditions of the Kyrgyz people as at koyu (to give a name), beshik termetuu (to rock the cradle), tusho kesuu (the rite of circumcision), soyko saluu (to wear earrings), konok tosuu (to meet guests) and bata beruu (blessing).
Keywords: менталитет; социальный характер; национальные традиции; mentality; эмоциональное вдохновение; national traditions; social character; emotional inspiration